Step
*
1
2
1
5
of Lemma
respects-equality-list
1. A : Type
2. B : Type
3. respects-equality(A;B)
4. n : ℤ
5. 0 < n
6. ∀x,y:Base.
((x = y ∈ {as:A List| ||as|| = (n - 1) ∈ ℤ} )
⇒ (x ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} )
⇒ (x = y ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} ))
7. x : Base
8. y : Base
9. x = y ∈ {as:A List| ||as|| = n ∈ ℤ}
10. x ∈ {bs:B List| ||bs|| = n ∈ ℤ}
11. tl(x) = tl(y) ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ}
⊢ x = y ∈ {bs:B List| ||bs|| = n ∈ ℤ}
BY
{ ((D 3 With ⌜hd(x)⌝ THENW Auto) THEN InstHyp [⌜hd(y)⌝] (-1)⋅) }
1
.....wf.....
1. A : Type
2. B : Type
3. n : ℤ
4. 0 < n
5. ∀x,y:Base.
((x = y ∈ {as:A List| ||as|| = (n - 1) ∈ ℤ} )
⇒ (x ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} )
⇒ (x = y ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} ))
6. x : Base
7. y : Base
8. x = y ∈ {as:A List| ||as|| = n ∈ ℤ}
9. x ∈ {bs:B List| ||bs|| = n ∈ ℤ}
10. tl(x) = tl(y) ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ}
11. ∀y:Base. ((hd(x) = y ∈ A)
⇒ (hd(x) ∈ B)
⇒ (hd(x) = y ∈ B))
⊢ hd(y) ∈ Base
2
.....antecedent.....
1. A : Type
2. B : Type
3. n : ℤ
4. 0 < n
5. ∀x,y:Base.
((x = y ∈ {as:A List| ||as|| = (n - 1) ∈ ℤ} )
⇒ (x ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} )
⇒ (x = y ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} ))
6. x : Base
7. y : Base
8. x = y ∈ {as:A List| ||as|| = n ∈ ℤ}
9. x ∈ {bs:B List| ||bs|| = n ∈ ℤ}
10. tl(x) = tl(y) ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ}
11. ∀y:Base. ((hd(x) = y ∈ A)
⇒ (hd(x) ∈ B)
⇒ (hd(x) = y ∈ B))
⊢ hd(x) = hd(y) ∈ A
3
.....antecedent.....
1. A : Type
2. B : Type
3. n : ℤ
4. 0 < n
5. ∀x,y:Base.
((x = y ∈ {as:A List| ||as|| = (n - 1) ∈ ℤ} )
⇒ (x ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} )
⇒ (x = y ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} ))
6. x : Base
7. y : Base
8. x = y ∈ {as:A List| ||as|| = n ∈ ℤ}
9. x ∈ {bs:B List| ||bs|| = n ∈ ℤ}
10. tl(x) = tl(y) ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ}
11. ∀y:Base. ((hd(x) = y ∈ A)
⇒ (hd(x) ∈ B)
⇒ (hd(x) = y ∈ B))
⊢ hd(x) ∈ B
4
1. A : Type
2. B : Type
3. n : ℤ
4. 0 < n
5. ∀x,y:Base.
((x = y ∈ {as:A List| ||as|| = (n - 1) ∈ ℤ} )
⇒ (x ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} )
⇒ (x = y ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ} ))
6. x : Base
7. y : Base
8. x = y ∈ {as:A List| ||as|| = n ∈ ℤ}
9. x ∈ {bs:B List| ||bs|| = n ∈ ℤ}
10. tl(x) = tl(y) ∈ {bs:B List| ||bs|| = (n - 1) ∈ ℤ}
11. ∀y:Base. ((hd(x) = y ∈ A)
⇒ (hd(x) ∈ B)
⇒ (hd(x) = y ∈ B))
12. hd(x) = hd(y) ∈ B
⊢ x = y ∈ {bs:B List| ||bs|| = n ∈ ℤ}
Latex:
Latex:
1. A : Type
2. B : Type
3. respects-equality(A;B)
4. n : \mBbbZ{}
5. 0 < n
6. \mforall{}x,y:Base. ((x = y) {}\mRightarrow{} (x \mmember{} \{bs:B List| ||bs|| = (n - 1)\} ) {}\mRightarrow{} (x = y))
7. x : Base
8. y : Base
9. x = y
10. x \mmember{} \{bs:B List| ||bs|| = n\}
11. tl(x) = tl(y)
\mvdash{} x = y
By
Latex:
((D 3 With \mkleeneopen{}hd(x)\mkleeneclose{} THENW Auto) THEN InstHyp [\mkleeneopen{}hd(y)\mkleeneclose{}] (-1)\mcdot{})
Home
Index